Gas phase hydrogenation of furfural to obtain valuable products using commercial Cr-free catalysts as an environmentally sustainable alternative to copper chromite. Issue 4 (August 2021) - Jiménez-Gómez, C.P.; Cecilia, J.A.; García-Sancho, C.; Moreno-Tost, R.; Maireles-Torres, P.
Abstract: Traditionally, copper chromite has been used in furfural hydrogenation to obtain valuable products, like furfuryl alcohol. However, the presence of Cr poses serious environmental issues, in such a way that different Cr-free catalysts have been proposed as alternative. In this work, two commercial Cu-based catalysts without Cr, currently used in alcohol reforming (R120) and water-gas shift (W220), have been successfully evaluated in FUR hydrogenation to produce selectively furfuryl alcohol. Both R120 and W220 catalysts were characterized, with special emphasis on the elucidation of metallic properties, dispersion and oxidation states of Cu species, and compared to copper chromite. The R120 catalyst attained the best catalytic performance and stability over time, reaching a turnover frequency (TOF) of 0.31 s −1 at 190 °C, after 1 h of reaction. The catalytic results demostrated that these Cr-free commercial catalysts have high potential to replace copper chromite as shown the stability test for 24 h. Graphical Abstract: ga1 Highlights: Commercial Cr-free catalysts have shown excellent behavior in the furfural hydrogenation. Strong interaction between Cu and ZnO particles leads to a higher activity and stability along the TOS. ZnO has an electronic promoter effect on the Cu 0, while Al2 O3 stabilizes the Cu particles. The presence of Lewis acid sites (Cu + ) favors the formation of carbonaceous deposits. Metal-sites are involved in the hydrogenation reaction, while acid sites influence in the hydrogenolysis reaction.